Does the angulation of the mandibular third molar influence the fragility of the mandibular angle after trauma to the mandibular body? A three-dimensional finite-element study. Issue 7 (19th May 2018) - Kılınç, Yeliz; Zor, Zeynep Fatma; Tümer, Mehmet Kemal; Erkmen, Erkan; Kurt, Ahmet
Abstract: The relationship between mandibular third molar (M3) angulation and mandibular angle fragility is not well established. The aim of this study was to evaluate the impact of M3 angulation on the mandibular angle fragility when submitted to a trauma to the mandibular body region. A three-dimensional (3D) mandibular model without M3 (Model 0) was obtained by means of finite-element analysis (FEA). Four models were generated from the initial model, representing distoangular (Model D), horizontal (Model H), mesioangular (Model M) and vertical (Model V) angulations. A blunt trauma with a magnitude of 2000 N was applied perpendicularly to the sagittal plane in the mandibular body. Maximum principal stress ( P max ) (tensile stress) values were calculated in the bone. The lowest P max stress values were noted in Model 0. When the M3 was present extra stress fields were found around marginal bone of second molar and M3. Comparative analysis of the models with M3 revealed that the highest level of stress was found in Model V, whereas Model D showed the lowest stress values. The angulation of M3 affects the stress levels in the mandibular angle and has an impact on mandibular fragility. The mandibular angle becomes more fragile in case of vertical impaction when submitted to a trauma to the mandibular body region.